Heteropoly acid-encapsulated metal–organic framework as a stable and highly efficient nanocatalyst for esterification reaction. Issue 29 (24th May 2019) - Zhang, Qiuyun; Yang, Tingting; Liu, Xiaofang; Yue, Caiyan; Ao, Liufang; Deng, Taoli; Zhang, Yutao
Abstract : Silicotungstic acid (HSiW) encapsulated UiO-66 nanocatalyst have been successfully synthesized by one-pot synthesis strategy and used as a stable and highly efficient catalyst for esterification. Abstract : Metal–organic frameworks (MOFs) have been shown to be promising candidates in the recent decades for the immobilization of guest active species due to their diversified structures, porosity, and high surface area. In this study, silicotungstic acid (HSiW) encapsulated UiO-66 has been successfully synthesized by one-pot synthesis strategy. The synthesized composite (HSiW-UiO-66) was characterized by X-ray diffraction (XRD), Fourier transform infrared spectrometry (FT-IR), nitrogen adsorption–desorption isotherms, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and thermogravimetric (TG) techniques, and the HSiW-UiO-66 was also employed as a solid acidic catalyst for the synthesis of biodiesel by esterification of lauric acid with methanol. The results revealed that the HSiW-UiO-66 composite had better textural properties (such as large BET surface area (758.3 m 2 g −1 ), large pore volume (0.438 cm 3 g −1 ), and smaller particle size (about 50–200 nm)), good thermal stability, and high catalytic activity. In addition, the effect of the esterification process parameters on biodiesel production was analyzed using single factor experimental method combined with response surface methodology (RSM); a high conversion of 80.5% with single factor optimization and 92.8% with RSM was obtained. More importantly, the conversion of lauric acid decreased from 80.5% to just 70.2% when the catalyst had been reused six times, which exhibited that the catalyst had excellent reusability. The high activity of HSiW-UiO-66 benefited from low activation energy of 27.5 kJ mol −1 . This work thus offers an underlying application for green biodiesel obtained from free fatty acids esterification or pre-esterification of low-cost oils with high acid value.